Apprentice needed - Skye, Obert (Skye, Obert. Wizard for hire (Series), 2019)
Ozzy thinks his life is finally becoming normal until someone delivers a mysterious plane ticket, and Ozzy, Sigi, and Clark find themselves in dire need of a wizard again.